Females in Corporate Board Diversity and Its Impact on Earnings Quality - Ardillah, Kenny (Universitas Padjadjaran, 2024)
Earnings quality is formed on corporate governance. The company's internal governance mechanism consists of the president director, the finance director, the board of directors, commissioners, and the audit committee. However, there is still a lack of studies exploring the relationship between female in-board diversity and earnings quality, especially in Indonesia. It is because Indonesia has a unique corporate governance system, even though Indonesia follows a corporate governance system on the European continent, namely the two-tier boards. This study aims to determine the influence of female president directors, female finance directors, female board of directors, female board of commissioners, and female audit committee on earnings quality. The sample of this study is manufacturing companies listed on the Indonesia Stock Exchange. Samples were selected using the purposive sampling method, and 70 companies were selected as research samples with a total data collection of 350 data from the research period of 2018-2022. Data analysis in this research uses multiple linear regression. The results of this study indicate that the presence of a female president director, a female finance director, and a female board of commissioner negatively affects earnings quality. On the other hand, the presence of the female board of directors has a positive effect on earnings quality. The female audit committee does not affect earnings quality. The author can conclude that the female gender still does not play an important role in the company's management to increase earnings quality because female’s behavior is more callous and not more assertive than male.